Proceso de atención de enfermería en adolescente de 16 años con sepsis puerperal. - Miño Plaza, Elisa Rashell (2021)
The purpose of this clinical case study is to apply the nursing care process to an adolescent patient with puerperal sepsis, evaluating and emphasizing the causes, clinical picture and possible complications that would arise if care is not provided in a timely manner. Reason why, as a nurse, we are able to evaluate each patient by putting all the theoretical - practical knowledge in order to recover the patient's health, applying the Nursing Care Process as a scientific method. In this case, the patient presented 2 days postpartum due to emergency presenting hyperthermia of 39ºC, diaphoresis and pain in the abdominal area between the umbilical and hypogastric quadrants. At the time of physical examination, purulent AND fetid transvaginal discharge was evidenced. The doctor indicates a complete blood count, vaginal discharge culture, urine culture, blood culture, abdominal and pelvic ultrasound. The assessment by functional patterns was carried out, to detect the affectations by systems and devices that are compromised with the state of health of the patient in order to be able to elaborate a specific care plan. A strict monitoring and control will also be granted in the personal and pharmacological treatment of the patient. Using essential tools for its elaboration, such as the taxonomies Nanda (diagnoses), Nic (interventions) and Noc (results), in order to fulfill our objectives proposed in this clinical case study.